Recent developments in the fire retardancy of polymeric materials - Cai, Gui-Peng (2014)
The widespread applications of polymeric materials require the use of conventional flame retardants based on halogen and phosphorous compounds to satisfy fire safety regulatory standards. However, these compounds, particularly halogen-based examples, are persistent organic pollutants of global concern and generate corrosive/toxic combustion products. To account for eco-friendliness, ultimate mechanical/physical properties and processing difficulties, the window of options has become too narrow. Although the incorporation of non-toxic nanofillers in polymers shows positive potential towards flame retardancy, many obstacles remain. Moreover, most of the literature on these materials is qualitative, and often points to conflicting/misleading suggestions from the perspectives of short-term and long-term fire exposure tests. Hence, there is a renewed need to fundamentally understand the fire response of such materials, and complement experimental results with theoretical modelling and/or numerical simulation.